Carrying capacity to preserve biodiversity on ecotourism in Mount Rinjani National Park, Indonesia - PIPIN NOVIATI SADIKIN; HADI SUSILO ARIFIN; BAMBANG PRAMUDYA; SRI MULATSIH (Biodiversitas Journal of Biological Diversity, 2017)
Sadikin PN, Arifin HS, Pramudya B, Mulatsih S. 2017. Carrying capacity to preserve biodiversity on ecotourism in Mount Rinjani National Park, Indonesia. Biodiversitas 18: 978-989. Mount Rinjani National Park (MRNP) in West Nusa Tenggara, Indonesia has applied ecotourism which becomes more popular at international and national level. Yet, the MRNP ecotourism faces various problems such as ecotourism resources damage, erosion, or garbage left by ecotourism activities, etc. This study aims to analyze (i) the land suitability for ecotourism based on criteria of tourism object range, land use and land cover, zone type, biodiversity range, and slope, and (ii) carrying capacity of the ecotourism area, the total number of visitors who can enjoy ecotourism attraction based on activities type, total area, capacity days, and turnover factor. The results of the land suitability for ecotourism analysis show that the MRNP ecotourism has been applied on the suitable land for ecotourism, except in Pelawangan Senaru and at the Peak of Mount Rinjani due to its sensitive and fragile area. The carrying capacity assessment using Douglass formula (1982) has counted the visitors for up to 42.527 visitors per year for camping activity. Generally, this value is under the average actual visitors at present, i.e. 44.112 visitors per year. It means the MRNP ecotourism is already exceeded its carrying capacity.